The use of whatsapp as a collaborative tool in vocabulary learning among tertiary level students - Kasturi, Sivabalan (2023)
Vocabulary is a central element of language proficiency that offers a strong foundation for students’ language skills. However, an extensive review of previous studies showed that Malaysian students' English proficiency levels are decreasing due to limited vocabulary knowledge despite having been exposed to the vocabulary for more or less than 11 years. In order to tackle students’ eagerness to acquire vocabulary, instructors are to be creative and aware of the current changes in the teaching and learning process. The mushrooming of technologies, including mobile phones, has made them widely used devices in modern society and a great influence in the education field. The use of instant messaging mobile applications has become epidemic among Generation Z (Gen-Z) because they spend a significant amount of their free time browsing through social network applications, such as WhatsApp. Hence, this study explored the use of WhatsApp as a collaborative learning tool to assist tertiary-level students in vocabulary learning. A total of 20 second-semester psychology students from Widad University College were involved in the study. This study aims to examine the effects of WhatsApp instruction and investigate the benefits and obstacles experienced by the students upon the use of WhatsApp in vocabulary learning. Furthermore, the quasi-experimental design employed in this study lasted for six weeks. A vocabulary test was used to gather quantitative data, while a focus group interview was conducted to collect qualitative data. SPSS version 22 was applied to analyse the quantitative data, while NVivo 12 was employed to evaluate the qualitative data. The findings of the quantitative data demonstrated a significant difference in the total mean scores between the pre-test and post-test after the use of WhatsApp in vocabulary learning. The focus group interview showed that the benefits of the use of WhatsApp were present, given that the application facilitated vocabulary learning, promoted collaborative learning, enhanced relationships among teachers and peers, boosted student confidence, and provided the students with technical and educational assistance in mastering the target vocabulary. Overall, the findings imply that WhatsApp is a suitable collaborative learning tool for assisting vocabulary learning. However, some techniques need to be improved to get around the problems and ensure that WhatsApp is a useful tool for vocabulary learning.